Functional Diversification Analysis of Soybean Malectin/Malectin-Like Domain-Containing Receptor-Like Kinases in Immunity by Transient Expression Assays - Zhang, Qian; Chen, Shuxian; Bao, Yazhou; Wang, Dongmei; Wang, Weijie; Chen, Rubin; Li, Yixin; Xu, Guangyuan; Feng, Xianzhong; Liang, Xiangxiu; Dou, Daolong (Frontiers in Plant Science, 2022)
Plants have responded to microbial pathogens by evolving a two-tiered immune system, involving pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) and effector-triggered immunity (ETI). Malectin/malectin-like domain-containing receptor-like kinases (MRLKs) have been reported to participate in many biological functions in plant including immunity and resistance. However, little is known regarding the role of MRLKs in soybean immunity. This is a crucial question to address because soybean is an important source of oil and plant proteins, and its production is threatened by various pathogens. Here, we systematically identified 72 Glycine max MRLKs (GmMRLKs) and demonstrated that many of them are transcriptionally induced or suppressed in response to infection with microbial pathogens. Next, we successfully cloned 60 GmMRLKs and subsequently characterized their roles in plant immunity by transiently expressing them in Nicotiana benthamiana, a model plant widely used to study host-pathogen interactions. Specifically, we examined the effect of GmMRLKs on PTI responses and noticed that a number of GmMRLKs negatively regulated the reactive oxygen species burst induced by flg22 and chitin, and cell death triggered by XEG1 and INF1. We also analyzed the microbial effectors AvrB- and XopQ-induced hypersensitity response and identified several GmMRLKs that suppressed ETI activation. We further showed that GmMRLKs regulate immunity probably by coupling to the immune receptor complexes. Furthermore, transient expression of several selected GmMRLKs in soybean hairy roots conferred reduced resistance to soybean pathogen Phytophthora sojae. In summary, we revealed the common and specific roles of GmMRLKs in soybean immunity and identified a number of GmMRLKs as candidate susceptible genes that may be useful for improving soybean resistance.